1980
DOI: 10.1111/j.1755-3768.1980.tb05743.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Thickness and Endothelial Damage After Intracapsular Cataract Extraction

Abstract: In a prospective study corneal thickness and specular microscopic findings of corneal endothelium are reported in 37 patients undergoing intracapsular cataract extraction. Central endothelial cell loss was estimated six months after the operation and was found to correlate significantly to the immediate post-operative increase in central corneal thickness. A subgroup of patients showing slight endothelial dystrophy prior to the operation showed a significantly higher increase in corneal thickness fourth day af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
11
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 20 publications
6
11
1
Order By: Relevance
“…The cause of this swelling remains unknown. A swelling of the same small magnitude has been found six months after intracapsular cataract extraction with a cell loss half of that found in the present study (Olsen 1980).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The cause of this swelling remains unknown. A swelling of the same small magnitude has been found six months after intracapsular cataract extraction with a cell loss half of that found in the present study (Olsen 1980).…”
supporting
confidence: 70%
“…Because of the quantitative association between cell loss and immediate corneal thickness increase after cataract extraction (Olsen 1980), this is to be expected. In the above mentioned studies, however, corneal thickness was found to return to normal levels some months after the operation.…”
mentioning
confidence: 97%
“…34 Similar to the observations of previous reports, we identified no significant difference in CCT based on gender in this study. [35][36][37] The relationship between CCT and age has been extensively studiedFalthough the majority of authors report a gradual decrease in CCT with advancing age after infancy, [38][39][40][41][42] in contrast, others have reported no change or an increase in CCT with advancing age. 36,43 The relationship between significant endothelial dysfunction and increased corneal thickness is well established, 3,[44][45][46] and recognized causes of increased corneal thickness include anterior segment disease and previous intraocular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…36,43 The relationship between significant endothelial dysfunction and increased corneal thickness is well established, 3,[44][45][46] and recognized causes of increased corneal thickness include anterior segment disease and previous intraocular surgery. 23,42,47,48 However, the relationship between corneal thickness and ECD in the normal eye throughout life has yet to be fully established, with few reports in the literature investigating a possible relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Since the normal endothelial cells are uniformly distributed between the central and peripheral cornea (Svedbergh & Bill 1972;Blackwell et al 1977;Sawa & Tanishima 1979), pre-operative evaluation can be made by observing the central endothelium alone. Hoffer (1979) and other investigators (Rao et al 1978;Olsen 1980;Mishima 1982;Azen et al 1983), however, have reported a definite regional differences in the endothelial cell density in eyes undergoing various cataract procedures. They showed that endothelial damage is much higher in the superior cornea where most surgical manipulations are performed.…”
mentioning
confidence: 92%